Evaluation of the Analgesic and Anti-inflammatory Activities of Some Thiazolo[4,5-d]pyrimidines - Balkan, Ayla; Gören, Zafer; Urgun, Hüsne; Çalιş, Ünsal; Çakar, A. Nur; Atilla, Pergin; Uzbay, Tayfun (Arzneimittelforschung, 2002)
Some thiazolo[4,5-d]pyrimidine-7(6H)-one derivatives were evaluated in vivo for their analgesic and anti-inflammatory activities. The results were compared with that of acetyl salicylic acid and phenylbutazone. Compounds 3b and 3h were the most active in the anti-inflammatory paw edema inhibition test. In terms of the analgesic activity (acetic acid writhing test), the most active compound was 2a followed by 31. The most active members of the series were investigated for their ED50 values and ulcerogenic potential.
Keywords: Anti-inflammatories, non-steroidal; Thiazolo[4,5-d]pyrimidines, analgesic activity, anti-inflammatory activity